2006
DOI: 10.1080/07481180600614351
|View full text |Cite
|
Sign up to set email alerts
|

Sense-Making, Grief, and the Experience of Violent Loss: Toward a Mediational Model

Abstract: Bereavement following violent loss by accident, homicide or suicide increases the risk for complications in grieving. This is the first study to examine a constructivist model of grief that proposes that sense-making, or the capacity to construct an understanding of the loss experience, mediates the association between violent death and complicated grief symptomatology. An ethnically diverse sample of 1,056 recently bereaved college students completed the Inventory of Complicated Grief (ICG) and questions asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
270
0
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 377 publications
(293 citation statements)
references
References 56 publications
13
270
0
10
Order By: Relevance
“…Building on previous research that demonstrated the mediating role of meaning making in the aetiology of PGD (Milman, Neimeyer, Fitzpatrick, MacKinnon, Muis, & Cohen, under review; Currier, Holland, & Neimeyer, 2006; Rozalski et al, 2017), the present study is the first to identify themes of meaning that prospectively predict PGD symptomatology in the context of violent loss. Specifically, relative to non-violent bereavement, participants grieving a violent death endorsed sense of peace and continuing bonds to a lesser degree and, over time, those who reported lower levels of these meaning themes experienced higher PGD symptomatology.…”
Section: Discussionmentioning
confidence: 88%
“…Building on previous research that demonstrated the mediating role of meaning making in the aetiology of PGD (Milman, Neimeyer, Fitzpatrick, MacKinnon, Muis, & Cohen, under review; Currier, Holland, & Neimeyer, 2006; Rozalski et al, 2017), the present study is the first to identify themes of meaning that prospectively predict PGD symptomatology in the context of violent loss. Specifically, relative to non-violent bereavement, participants grieving a violent death endorsed sense of peace and continuing bonds to a lesser degree and, over time, those who reported lower levels of these meaning themes experienced higher PGD symptomatology.…”
Section: Discussionmentioning
confidence: 88%
“…This positive coping effect of meaning has been found for a broad variety of extreme adversities, such as coping with the horrifying experiences as a prisoner in a Nazi concentration camp (Frankl, 1963), loss of family members (Davis, Nolen-Hoeksema, & Larson, 1998), loss of a child by the sudden infant death syndrome (McIntosh et al, 1993), severe injuries (Bulman & Wortman, 1977), experiences of violence (Currier, Holland, & Neimeyer, 2006), and terrorism (Updegraff et al, 2008). The positive effects of meaning on coping with adversity have been mainly explained by two processes: (a) meaning provides people with an increased sense of control and security (Heider, 1958;Kelley, 1967), which makes the world more predictable (Roese & Olson, 1996), and (b) meaning attenuates the emotional intensity of unexpected events (Wilson, Centerbar, Kermer, & Gilbert, 2005;Wilson, Gilbert, & Centerbar, 2003; for an overview, see also Updegraff et al, 2008).…”
Section: Meaning and Coping With Terrorist Threatmentioning
confidence: 99%
“…That is, within the criteria proposed by both Horowitz et al and Prigerson and colleagues, there is little to no recognition of the complex factors that impact on the experience of grief. Indeed, empirical research clearly demonstrates that the dominant discourse does not adequately capture the grief experiences of many groups, such as bereaved parents and those bereaved through violent means (e.g., Breen, 2007;Currier, Holland, & Neimeyer, 2006;Doka, 1996;Harwood, Hawton, Hope, & Jacoby, 2002;Lord, 2000;Murphy, Johnson, Wu, Fan, & Lohan, 2003;Riches & Dawson, 2000;Rosenblatt, 2000). Yet, no distinction is made between their description of grief in their samples, which were primarily widows and widowers bereaved following the life-threatening illnesses of their spouses (e.g., Chen et al, 1999;Prigerson et al, 1995Prigerson et al, , 1996Prigerson et al, , 1997Schlernitzauer et al, 1998; see also Hogan et al, 2003Hogan et al, -2004Prigerson & Maciewjewski, 2005-2006, and the subsequent prescription of these "normal" and "complicated" reactions to different samples.…”
Section: Medicalization Of Griefmentioning
confidence: 99%